Participation against Populism: Participatory Design Approaches in Residential Areas in the Context of Social Sustainability - Oskay, Berkay; Barkul, Omur (KARE PUBL, 2022)
The principle of participation has an important role in maintaining social sustainability. In recent years, debates on participatory planning and participatory design practices have come to the fore in the creation of liveable environments for everyone in terms of architecture and planning disciplines. Participatory design and planning practices, which have risen against the representation crisis driven in liberal democracies since the 1960s, have lost momentum while the neoliberal doctrines have become determinant over time, and capital flows have become the most important factor that determines the urban space, and reduced the societies to the communities who cannot have a say on their environments. It is seen that the common demands of urban opposition movements, which are spreading around the world and in Turkey, against the rise of illiberal populist tendencies that have determined the widespread climate of the period since the 2000s, have been organized within the framework of the principle of participation. In this study, we discussed the role of the principle of participation in the construction of social sustainability and the importance of participatory mechanisms against the populist tendencies today in the theoretical background that constitutes the starting point of the study. Afterwards, we examined the participatory design principles, tools and participation typologies in planning and housing areas according to this framework. The unique aspect of the study is that it presents a descriptive framework that evaluates a current question. Thus, it is aimed to contribute to the participation literature, which is on the rise again in the immediate present.
Keywords: Participatory planning; participatory design; housing; social sustainability; sustainable development; Public Administration